Analysis of Production Line Balance with Helgeson Birnie Approach on Plastic Chopping Machine - Khatami, Muhammad; Ginting, Rosnani; Ishak, Aulia (TALENTA Publisher, 2023)
The purpose of track balance is to find out the constraints that cause the work station to be unbalanced. Research on plastic chopping tool products, where the production of plastic chopping tools takes too long in the process of making one product. line balancing is the process of balancing the production line, especially in the assembly production process. The balance of this path is intended to reduce excessive workload on one work station and strive so that each work station on each path has the same load. It is intended that each work station has a more efficient work cycle time and can avoid operator errors in assembly. to minimize the number of stations for a given cycle time. The problem of unbalanced production lines and differences in large station times causes an imbalance in the production floor. Balancing the lines on the production floor will affect the achievement of predetermined production targets. The Helgeson-Birnie method is one of the track balance methods that can solve problems in track balance. In the Ranked Position Weight results there are 6 work stations, the efficiency value is 90.02%, the balance delay is 9.97% and the Smoothing Index is 628,204